Human disposition of L-theanine in tea or aqueous solution - P.C. van der Pijl; L. Chen; T.P.J. Mulder (Journal of Functional Foods, 2010)
After consumption of tea, L-theanine enters systemic circulation and is assumed to enter the brain. Several human studies indicate that L-theanine influences brain functioning. Knowledge about the pharmacokinetics of L-theanine facilitates further study of this health effect. Volunteers received 25–100 mg of L-theanine as tea, as L-theanine-enriched tea, and as biosynthetic L-theanine in aqueous solutions. Plasma was analysed for L-theanine content after which data were fitted with a 1- compartment model. For all interventions, the lag time was approximately 10 min and half-lives of absorption and elimination were approximately 15 and 65 min respectively. After approximately 50 min, maximum plasma concentrations of between 1.0 and 4.4 mg/L were achieved. Maximum plasma concentration and area under the plasma-concentration–time curve were dose-proportional. This knowledge allows prediction of plasma concentrations for various dose regimens supporting further study of a health benefit of L-theanine.